Analisis Pengaruh Pengungkapan Sustainability Report dan Kinerja Keuangan Terhadap Kualitas Audit pada Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of sustainability report disclosure and financial performance on audit quality by including leverage, company size, and Public Accounting Firm (KAP) size as control variables. The study used a quantitative approach with an explanatory research design. The study population was non-financial companies listed on the Indonesia Stock Exchange for the 2020–2024 period, while the sample was determined using a purposive sampling technique based on the criteria of companies that consistently published audited financial statements and sustainability reports during the observation period. Data analysis was conducted using panel data regression after selecting the best model and testing the necessary assumptions. The results show that financial performance negatively affects audit report lag as a proxy for audit quality, indicating that companies with better financial performance tend to complete the audit process in a shorter time, thus improving the quality of their financial reporting. Conversely, sustainability report disclosure did not significantly affect audit quality. These findings indicate that the timeliness of audit completion is still more influenced by the company's financial condition than the extent of sustainability disclosure. Therefore, this information can be a consideration for management, auditors, and investors in evaluating the quality of company reporting.